1998
DOI: 10.1007/s002130050671
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine enhances sustained attention in the rat under specific task conditions

Abstract: Although nicotine has cognitive enhancing effects in both animals and humans, most studies in humans have only shown consistent improvements in sustained attention. Moreover, many studies with smokers have been criticised, since nicotine may simply be relieving withdrawal-induced deficits. The present study investigated the effect of nicotine on sustained attention in drug-naïve rats using a five-choice serial reaction time task. Initially, the task was demonstrated to satisfy some of the criteria for the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
159
6
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(191 citation statements)
references
References 32 publications
25
159
6
1
Order By: Relevance
“…fewer errors) than saline-treated rats. This finding is consistent with previous work reporting enhanced performance with nicotine treatment (Levin et al, 1990(Levin et al, , 1996% 1996bAbdulla et al, 1993;Mirza and Stolerman, 1998). However, nicotine treatment has also been shown to impair or have no effect on performance (Dunnett and Martel, 1990;Levin et al, 1997; reviewed by Levin and Simon, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…fewer errors) than saline-treated rats. This finding is consistent with previous work reporting enhanced performance with nicotine treatment (Levin et al, 1990(Levin et al, , 1996% 1996bAbdulla et al, 1993;Mirza and Stolerman, 1998). However, nicotine treatment has also been shown to impair or have no effect on performance (Dunnett and Martel, 1990;Levin et al, 1997; reviewed by Levin and Simon, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Performance after nicotine (a nicotinic acetylcholine receptor agonist) treatment was examined because of the recent interest in the effects of nicotine on learning and performance. For example, nicotine treatment can improve rats' performance in a radial-arm maze (Levin et al, 1990(Levin et al, , 1996a(Levin et al, , 1996b, a Morris water maze (Abdulla et al, 1993) and a five-choice serial reaction time task (Mirza and Stolerman, 1998). In each task, variability in performance existed in nicotinetreated groups as well as in the controls.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy was not altered in the present study, though some studies reported that the administration of nicotine enhanced attentional performance in the 5-CSRTT (Mirza and Stolerman 1998;Hahn et al, 2002;Bizarro et al, 2004). This discrepancy may be due to differences in the attentional demands of the task performed between previous studies and the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…This discrepancy may be due to differences in the attentional demands of the task performed between previous studies and the present study. Indeed, Mirza and Stolerman (1998) found a nicotine enhancement effect on attentional performance only when the attentional demands were increased by prolonging the ITI to 20 s, while some other studies found an effect of nicotine on attentional performance under standard tasks (Hahn et al, 2002;Bizarro et al, 2004). Although the 3-CSRTT is appropriate for a brief assessment of impulsive action, its sensitivity for detecting slight changes in attentional function may be somewhat restricted.…”
Section: Discussionmentioning
confidence: 95%
“…In rat (for reviews see Brioni et al, 1997;Levin and Simon, 1998) and monkey (for review see Buccafusco et al, 1996) models of nicotine-induced cognitive improvement is more clearly seen in terms of effects on memory performance than attention, although attentional performance has been documented to be improved by nicotine in some studies (Mirza and Stolerman, 1998;McGaughy et al, 1999;Stolerman et al, 2000). These animal models are vital for the determination of the mechanisms of nicotinic-induced cognitive improvement.…”
Section: Systemic Nicotine Effects On Memorymentioning
confidence: 99%